(untitled) (Heritage, 2022)
The paper presents research findings that emphasize the importance of collaborative learning as an effective approach to learning for deaf and hard of hearing students, as opposed to traditional. This educational approach illustrates how shared learning experiences can promote socialization and interaction, and facilitate learning and contribute to the quality of knowledge. Thus, collaborative learning is a modern strategy that contributes to alleviating the lack of traditional teaching in different types of the school environment. This research aims to experimentally determine the effects of cooperative learning in relation to traditional learning about the permanence of knowledge of deaf and hard of hearing students. The study sample consisted of 49 deaf and hard of hearing students aged 12 to 15 years. Specially designed knowledge tests for this research were used for data collection. The results showed that there is a statistically significant difference in the durability of knowledge of deaf and hard of hearing students acquired afterthe conducted experimental program, and the retest was conducted after six months.